Hubungan Risiko Manual Handling dan Karakteristik Individu dengan Keluhan Muskuloskeletal pada Petani Pembudidaya Ikan Lele Bangun Mina Sejahtera Kec. Sawit Kab. Boyolali - Hakim, Nurul Radhiyah, Tarwaka, PGDip.Sc., M.Erg, Rezania Asyfiradayati, SKM., MPH (2017)
Musculoskeletal Disorders is a pain on the parts of muscle skeletal when that pain starting from a very mild complaint until the very sick. If this condition occurs in a long time can reduce productivity and work efficiency. Preliminary study had been showed that 100% Bangun Mina Sejahtera catfish cultivating farmers have musculoskeletal disorders. This study aims to determine manual handling risks relevance with musculoskeletal complaints in catfish cultivating farmers Bangun Mina Sejahtera Kec. Sawit Kab. Boyolali. The type of this research is observational quantitative using cross sectional approach. The sample of this research are 32 catfish cultivating farmers with exhausted sampling technique. Measurements of manual handling work posture using REBA calculated excel method and measurement of musculoskeletal disorders using Nordic Body Map (NBM) table. Bivariate analysis using Rank Spearman with significant level (α≤0.050). Results for work posture with musculoskeletal disorders were obtained (p-value = 0.006) r=0.474 and results for individual characteristics with musculoskeletal complaints were (1) age (p-value = 0.011) r=0.446; (2) exercise habits (p-value = 0.157); (3) work period (p-value = 0.002) r=0.526; (4) BMI (p-value = 0.031) r=0.381 and (5) smoking habit (p-value = 0.002) r=0.526. Conclusion in this study there is a significant correlation between work posture, age, work period, BMI and smoking habits with musculoskeletal disorders and there is no significant correlation between exercise habits with musculoskeletal disorders. In recomended catfish cultivating farmers to warm up before starting work activities as well as the wholesaler provides manual handling tools and perform engineering addition of pads on containers that used during work activities occur.